New methods in diagnosis and therapyStroke following transcatheter aortic valve implantation. Is neuroprotection justified? - Dąbrowski, Maciej; Witkowski, Adam (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Degenerative aortic stenosis (AS) is the most frequent type of valvular heart disease. In patients with symptomatic AS surgical aortic valve replacement (SAVR) is a recommended treatment strategy. Due to a high risk of perioperative mortality, up to 30% of patients with AS are considered not suitable for SAVR. In the last 10 years dynamic development of transcatheter aortic valve implantation (TAVI) has been observed as an alternative to SAVR in patients with AS and high risk for surgery. In the two randomized trials published so far and numerous registries, stroke and transient ischemic attack still remain serious periprocedural complications after TAVI. Because the majority of these episodes are driven by microembolization during the procedure, different neuroprotection devices were developed and clinically tested. Embrella and SMT are deflector devices, using a microporous membrane mounted on a nitinol frame, designed to cover the ostia of the brachiocephalic trunk and the left carotid artery. The Claret System is designed to filter cerebral blood flow within the ostia of the brachiocephalic trunk, as well as in the left common carotid artery. Randomized clinical data have demonstrated that TAVI is associated with more neurological events compared to SAVR. However, to date the efficacy of the neuroprotection systems has not been assessed in randomized trials. Before we know the results of such trials, the use of the devices should be limited to patients at high risk of neurological complications, such as patients with previous stroke, massive calcification on aortic leaflets, annulus and porcelain aorta.